Deteksi Jenis Rempah-Rempah Menggunakan Metode Convolutional Neural Network Secara Real Time - Sanjaya, Mellynia; Nurraharjo, Eddy (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Spices are one of the products of natural wealth owned by Indonesia which has been recognized by the world. Spices are part of plants that have benefits not only as a complement to spices in cooking, but are also used to boost the immune system of living things. Due to the many types of spices that exist in Indonesia, a system is needed to help the community, especially millennial children, to know the various types of spices correctly and clearly. The spice detection process is carried out using an accuracy calculation on the system using a dataset in the form of 1800 images and 12 types of spices. The classification process for spices is generated using the Convolutional Neural Network (CNN) method with the tensorflow module used for the training and testing process of data. The results of the accuracy experiment on spices resulted in an accuracy value of recognizing the type of spice of 60%.